DETERMINANTS OF FIRM VALUE IN INDONESIA’S FINANCIAL SECTOR DURING THE POST-PANDEMIC TRANSITION - Vivi Apriliyani; Surya Raharja (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
The period of 2020–2023 marked a unique phase for Indonesia’s financial sector, characterized by post-pandemic recovery, accelerated digital transformation, and shifts in investor preferences away from traditional indicators such as firm scale and leverage. This study aims to examine the influence of capital structure, firm size, and profitability on firm value in this transitional context, highlighting how these factors operate differently in a dynamic and regulated market environment. This research employs a quantitative causal–explanatory design using panel data from 90 financial sector companies listed on the Indonesia Stock Exchange for the period 2020–2023. Firm value is measured by Price to Book Value (PBV), with capital structure proxied by Debt to Equity Ratio (DER), firm size by the natural logarithm of total assets, and profitability by Return on Equity (ROE). The findings reveal that profitability positively and significantly affects firm value, while firm size shows a significant negative effect, and capital structure has no significant impact. These results indicate that, in the post-pandemic recovery phase, investors prioritize operational performance and profitability over firm scale or leverage. The study offers theoretical contributions by re-examining classical financial theories in the context of an emerging economy and practical recommendations for corporate managers and investors to focus on enhancing profitability, agility, and innovation to sustain firm value.